Modular two-phase heat storage for Carnot Batteries - Regensburger, Christoph; Steger, Daniel; Schlücker, Eberhard (Energy Proceedings, 2020)
Carnot Batteries are a promising approach to store electrical energy in a thermal way. Besides the loading and unloading thermodynamic processes, the heat storage is a field of mayor interest in research. This paper presents an innovative modular storage setup that is easily scalable and contains an immiscible liquid phase to separate the hot and cold side of a sensible water storage. The separation of hot and cold side thus reduces the heat losses and improves the efficiency of the whole storage concept. A pilot plant to study the idea experimentally is in construction.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Carnot Battery; modular energy storage; sensible heat storage; thermal stratification; two-phase